Pengaruh Work Family Conflict Dan Stres Kerja Terhadap Kinerja Perawat Wanita Pada Blud Rumah Sakit Benyamin Guluh Kabupaten Kolaka - Epi Karlina; Fitri; Suwarto (CV. ITTC INDONESIA, 2023)
This study aims to determine: (1) the effect of Work Family Conflict on Nurse Performance at Benyamin Guluh Hospital BLUD, Kolaka Regency. (2) the effect of work Stress on the Performance of famale nurses at Benyamin Guluh BLUD Hospital, Kolaka Regency. This research uses a quantitative approach. Coleccting data in this syudy using interviews, literature study, anf distributing questionnaires. The sample used in this study were all married famale nurses as many as 122 respondents using the saturated census method. Testing the research instrument using the validity test anf reliability test with SPSS 2.0. The data analysis technique used in this study is the measurement model test (outer model) and the strutural model test (inner model) with Smart PLS 40. Based on the result of the study is know that there is a negative and significant influence between Work Family Conflict variabels on the performance of female nurses who are merried as indicated by the t-statistic value of 8.828 with a P-Value of 0.000. Meanwhile, the variable work stress has a negative ang significant effect on the performance of famale nurses as shown by the t-statistic value 2.208 with a P-value 0f 0.027.